Digital Transformation With the Impact of AI in Government Decision Making - Firman Freaddy Busroh; Fatria Khairo; Aprila Niravita; Bhanu Prakash Nunna (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
This abstract reviews digital transformation in the context of government decision making with respect to the impact produced by AI and the implications for constitutional law. Digital transformation has become the main driver in the industrial revolution that has swept across various sectors, including the government. The presence of AI in the governmental decision-making process provides an increase in efficiency, accuracy, and responsiveness in answering the complexity of the problems faced. However, the presence of AI in government decision making raises a number of legal questions that need to be taken into account. These issues are related to transparency, accountability, privacy, and fairness in applying the AI technology by the government. In the context of constitutional law, adjustments and improvements of regulations need to be made to accommodate the new dynamics introduced by digital transformation with the existence of AI. Therefore, it is important to undertake efforts to understand and predict the impact of AI in decision making by the government and its implications on constitutional law to direct the development of inclusive and sustainable public policy in this digital era.